House prices, home equity and entrepreneurships - Stefano Corradin; Alexander Popov (European Central Bank (ECB), 2013)
How does home ownership affect new business creation? We develop a model of career choice in the presence of liquidity constraints in which shocks to the value of real estate affect the propensity of potential entrepreneurs to borrow against the value of their property. Using a large US individual-level survey dataset over the 1996-2006 period, we show that a 10% increase in home equity raises the probability of transition into entrepreneurship by up to 14%. Our results persist when we use the topological elasticity of housing supply to generate variation in home equity that is orthogonal to entrepreneurial choice.
Keywords: G21; L26; 330; collateral channel; entrepreneurship; Home ownership